The geography of the Bible : a study in historical geography /. - Baly, Denis (New York : Harper & Brothers Publishers, 1957)
A trained geographer describes the historical geology, climate, vegetation and animal life of the lands of the Bible.
Bibliography: p. 273-282.
Keywords: Bible -- Geography